A Novel Ivermectin-Derived Compound D4 and Its Antimicrobial/Biofilm Properties against MRSA - Xinyi Tan; Haoji Xie; Bin Zhang; Jiale Zhou; Zhende Dou; Xiao Wang; Ning Wang (MDPI AG, 2021)
Methicillin-resistant Staphylococcus aureus (MRSA) and its biofilms infection is still a serious threat to global health. It is urgent to develop efficient drugs by repositioning or designing drugs to solve this problem. In this study, the antibacterial/biofilm activity and mechanisms of ivermectin (D) and its 4"-position amino substitution derivative (D4) against MRSA were investigated. The minimum inhibitory concentration (MIC) of D was 20 μg/mL, which is four times higher than D4 (MIC = 5 μg/mL). The mechanism research demonstrated that D4 was more potent than D at destroying bacterial cell wall, permeating cell membrane (6.25-36.0% vs 1.92-6.04%) and binding to MRSA genomic DNA. Moreover, after incubation with 10-40 μg/mL D4 for 24 h, the percentages of biofilm decreased by 21.2-92.9%, which was more effective than D (no significant change at 40 μg/mL). The antibiofilm effect is achieved by regulating the expression of related genes (RSH, relQ, rsbU, sigB, spA, and icaD). Additionally, though the higher hemolysis makes D4 a safety risk for intravenous injection, other administration options could be considered as well. Therefore, all the results have indicated that D4 may be a potential candidate compound for the treatment of MRSA and its biofilm infections.